A Conceptual Framework of Antecedents of Service Loyalty in Health Care: Patients' Perspective. (January 2019) - George, Ajimon; Sahadevan, Jobin
As the health care sector in India is becoming more and more competitive, researchers and practitioners are getting increasingly interested in exploring how post-purchase behaviour of patients can be managed and high level of patient loyalty can be ensured. Patient loyalty has gained immense importance in health care service sector in India because of the drastic changes that have taken place in health care market in the last two decades. Today, the health care market is characterized by intense competition and specialization. Hospital management is increasingly recognizing the need to focus on patient loyalty as a means to achieve profitability and also to improve their competitive position. In this article, we theoretically explore the relationship of the antecedents of patient loyalty (service quality, perceived value, corporate image and perceived price fairness) and its outcomes (patients' satisfaction and patient loyalty). The outcome of this research is a conceptualization of antecedents of patients' loyalty in the context of health care supported by research propositions based on the existing literature. The article contributes to the existing literature a hypothesized model that permits the examination of consumer behavioural procedures with regard to service quality, perceived value, perceived price fairness, corporate image, patient satisfaction and patient loyalty. Exploring these processes through empirical studies in future will provide new insights, which will help hospital management retain existing customers and attract new customers.